Healthy lifestyles in pre-service teachers in Israel: the impact of academic institutions - Ahdut-HaCohen, Ronit; Carmel, Paz (Frontiers in Public Health, 2023)
Purpose This study examines the impact of academic institutions on changes to students’ awareness and habits regarding a healthy lifestyle, specifically through nutrition and physical exercise, following the Covid-19 pandemic. Design and subjects In May 2020, quantitative online questionnaires were completed by 266 pre-service teachers (83.5% female), aged 19–63, who were studying at an academic institution in Israel. Setting The questionnaire, which included health-related 15 items, as well as a number of demographic questions, was distributed via social media, academic mailing lists, and the researchers’ colleagues. Methods The respondents were asked to provide socio-demographic data and information regarding their health-related habits, such as smoking and exercising, at two timepoints: prior to the Covid-19 pandemic and during the first lockdown in Israel (March–May 2020). Analysis Statistical analysis included paired t-tests, Wilcoxon and McNemar tests, Pearsons’s correlations, and hierarchical regressions. Results The academic institution’s promoting of a healthy lifestyle, as perceived by students, was found to contribute to the explained variance (EPV) of their maintaining a healthy lifestyle, prior to and during the Covid-19 pandemic (R2 = 9.4%, p < .001and R2 = 2.4%, p = 0.009, respectively), beyond the respondents’ demographic characteristics. Moreover, correlations were found between the institution’s promoting of a healthy lifestyle at both timepoints. Respondents who perceived their institution as promoting a healthy lifestyle prior to the pandemic maintained healthier lifestyles than their peers; healthier lifestyles were also maintained by respondents who were unmarried, non-smokers, more educated, and watched less television. Finally, the institution’s promoting of a healthy lifestyle prior to the pandemic significantly contributed to the students’ maintaining a healthy lifestyle and healthy nutrition during the pandemic. Conclusion The findings of this study highlight the impact of academic institutions on maintaining healthy lifestyles, even in times of crises and emergencies, thereby contributing to public health.